Deletion of an X-inactivation boundary disrupts adjacent gene silencing. - Lindsay M Horvath (Public Library of Science (PLoS), 2013)
In mammalian females, genes on one X are largely silenced by X-chromosome inactivation (XCI), although some "escape" XCI and are expressed from both Xs. Escapees can closely juxtapose X-inactivated genes and provide a tractable model for assessing boundary function at epigenetically regulated loci. To delimit sequences at an XCI boundary, we examined female mouse embryonic stem cells carrying X-linked BAC transgenes derived from an endogenous escape locus. Previously we determined that large BACs carrying escapee Kdm5c and flanking X-inactivated transcripts are properly regulated. Here we identify two lines with truncated BACs that partially and completely delete the distal Kdm5c XCI boundary. This boundary is not required for escape, since despite integrating into regions that are normally X inactivated, transgenic Kdm5c escapes XCI, as determined by RNA FISH and by structurally adopting an active conformation that facilitates long-range preferential association with other escapees. Yet, XCI regulation is disrupted in the transgene fully lacking the distal boundary; integration site genes up to 350 kb downstream of the transgene now inappropriately escape XCI. Altogether, these results reveal two genetically separable XCI regulatory activities at Kdm5c. XCI escape is driven by a dominant element(s) retained in the shortest transgene that therefore lies within or upstream of the Kdm5c locus. Additionally, the distal XCI boundary normally plays an essential role in preventing nearby genes from escaping XCI.